2021
DOI: 10.3389/fnins.2020.615395
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Alleviates Chronic Pain-Induced Anxiety Disorders by Regulating the rACC-Thalamus Circuitry

Abstract: Anxiety is a common comorbidity associated with chronic pain, which results in chronic pain complexification and difficulty in treatment. Electroacupuncture (EA) is commonly used to treat chronic pain and anxiety. However, the underlying mechanisms of the EA effect are largely unknown. Here, we showed that a circuitry underlying chronic pain induces anxiety disorders, and EA can treat them by regulating such circuitry. Using chemogenetic methods, we found that chemogenetic activation of the rostral anterior ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
1
30
1
Order By: Relevance
“…While anxiety-like behaviors were relieved by EA, the anxiolytic effect could not be reversed by activating the rACC Glu -vlPAG pathway. In contrast, our previous study has revealed that inhibition of the rACC Glu -thalamus circuit alleviated anxiety-like behaviors in CFA rat models but did not affect the mechanical pain threshold (Shen et al, 2020). Furthermore, activation of the rACC Glu -thalamus pathway specifically reversed the anxiolytic effect of EA in CFA rat models but had no effect on pain sensation.…”
Section: Discussioncontrasting
confidence: 80%
“…While anxiety-like behaviors were relieved by EA, the anxiolytic effect could not be reversed by activating the rACC Glu -vlPAG pathway. In contrast, our previous study has revealed that inhibition of the rACC Glu -thalamus circuit alleviated anxiety-like behaviors in CFA rat models but did not affect the mechanical pain threshold (Shen et al, 2020). Furthermore, activation of the rACC Glu -thalamus pathway specifically reversed the anxiolytic effect of EA in CFA rat models but had no effect on pain sensation.…”
Section: Discussioncontrasting
confidence: 80%
“…Another animal study showed that injection of an excitatory glutamate antagonist into the ACC prevented formalin-induced positional aversion without relieving formalin-induced acute inflammatory pain ( Johansen and Fields, 2004 ). In addition, our previous study found that inhibiting glutamatergic neurons in the ACC-thalamic neural circuity can interfere with pain-induced anxiety-related emotions ( Shen et al, 2020 ). There is no doubt that all of this evidence suggests that hyperexcitability of the ACC is involved in pain and pain-related negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The modern clinical application of acupuncture involves the use of an electrical stimulator to produce increased signal and response mechanisms within the central nervous system [ 20 ]. The application of this stimulating method, known as electroacupuncture (EA), has displayed a proficient aptitude in the treatment of a large variety of chronic pain conditions [ 21 , 22 ], as well as several psychological conditions [ 16 ]. Furthermore, the neurological signaling cascades involved in the mediation of CPDC can be activated through ST36 (zusanli), a TRPV1 responding mechanosensitive acupoint generally used in clinical regimes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%